1999
DOI: 10.1088/0022-3727/32/9/307
|View full text |Cite
|
Sign up to set email alerts
|

The structural behaviour of layers of SnS grown by spray pyrolysis

Abstract: Thin layers of tin monosulphide have been grown from equimolar solutions of tin chloride and N,N-dimethyl thiourea on Corning 7059 glass substrates at various temperatures in the range 100-450 °C using spray pyrolysis. The structural properties have been determined by using x-ray diffraction and scanning electron microscopy to evaluate the crystalline phases present and the surface topography of the grown layers. The changes observed in the structural phases with the growth temperature during the film formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 13 publications
1
7
0
4
Order By: Relevance
“…In 1971, Patil and Tredgold [5] studied the first single crystals of SnS 2 prepared by vapour transport (VT) method and yielded interesting spectral response of photoconductivity measurements which showed a band gap of 2.34 eV (at 300 K). These results were confirmed by the works of Koteswara Reddy et al [6] who investigated thin layers of tin monosulfide grown at various temperatures in the range 100-450 • C using spray pyrolysis. They carried out an interesting study of the changes observed in the structural phases with the growth temperature during the film formation.…”
Section: Introductionsupporting
confidence: 76%
“…In 1971, Patil and Tredgold [5] studied the first single crystals of SnS 2 prepared by vapour transport (VT) method and yielded interesting spectral response of photoconductivity measurements which showed a band gap of 2.34 eV (at 300 K). These results were confirmed by the works of Koteswara Reddy et al [6] who investigated thin layers of tin monosulfide grown at various temperatures in the range 100-450 • C using spray pyrolysis. They carried out an interesting study of the changes observed in the structural phases with the growth temperature during the film formation.…”
Section: Introductionsupporting
confidence: 76%
“…Bundan dolayı SnS2 de oluşan arayüzler üzerine yapılacak kontaklar için çok iyi elektronik geçişler yapmasına olanak sağlar [4]. Kalay ve kükürdün doğada bol olması ve toksik olmamamsı da önemli avantajlarındandır [5,6]. SnS2 ince filmleri fotodedektörlerde [7], gas sensörlerinde [8], güneş pillerinde [9], lityum iyon bataryalar için elektrot olarak [10], transistörlerde [11], diyotlarda [12] süperiletken aygıtlarda [13] vs. gibi birçok alanda kullanılmaktadır.…”
Section: Introductionunclassified
“…The films have mainly been deposited by molecular beam epitaxy [9], chemical bath deposition [10], spray pyrolysis [11], rf sputtering [12], and evaporation [13]. As a wet-based novel approach, electrodeposition [14][15][16] has been suggested due to its simple and low cost deposition.…”
Section: Introductionmentioning
confidence: 99%